Winter's Song - Spence, Stephanie; Jose, Gladys (New York, NY Tangerine Press, 2016)
"It's been a while since anyone has sung 'Winter's Song' well enough to bring in North Wind and his extra-frosty weather, and Snowfall has been slowly melting away. Will sibling snowballs Puff and Pearl find the courage to sing for the North Wind and save Snowfall, or will it be lost forever?"--Back cover
113865
Keywords: Siblings; Courage; Singing; Winter; Snow